SOCIAL CONTROL AND THE ESCALATION OF SEXUAL CRIMES AGAINST CHILDREN IN THE LATE-MODERNITY ERA: A CRIMINOLOGICAL ANALYSIS IN INDONESIA - Nur Arief Kurniawan; Muhammad Mustofa (SOSIOEDUKASI, 2026)
Sexual violence against children has become an alarming phenomenon in late modernity. This study aims to explore the root causes of sexual violence against children through the lens of social control and typology of violence based on empirical data from 2020 to 2025. Using qualitative methods, this article elaborates on data from Simfoni PPA as well as Martin Innes' social control theory and J. Conrad's typology of violence. The results of the analysis show a consistent upward trend in cases nationally and in DKI Jakarta, which is an indicator of the failure of social control mechanisms. This study concludes that criminal policy must shift from a moral panic response to a rehabilitative, re-educational, and perpetrator profiling approach based on scientific data. These findings emphasise the urgency of reformulating child protection policies that are not solely oriented towards repressive measures, but focus on strengthening preventive social control at the family and community levels, integrating data-based reporting systems, and developing measurable rehabilitation and re-education programmes for perpetrators. In addition, risk-based policy design and spatial analysis are needed to strengthen early detection, narrow opportunities for crime in the domestic sphere, and increase the effectiveness of systemic and sustainable state intervention.